Non- Mental Components in the Immaterial Element of Crime A Critique to the Design of the Main Elements of the Crime - Reza Zahravi; Seyed Ali Kazemi; Rasool Ahmadzadeh (پژوهش‌نامۀ انتقادی متون و برنامه‌های علوم انسانی)
A delinquent, in a deliberate crime, must have the mental intention and also the knowledge necessary to commit the crime, or in doing a crime, without a definite intention to commit an offense, he/she makes an error that could qualify him/her for criminal responsibility. But this does not encompass all that is called the immaterial element, and only contains part of what is called the immaterial mental elements, while it is indispensable that the other part of the spiritual element that is "immaterial" and at the same time "non-mental" be identified independently and have the opportunity to be appeared and emerged. The authors try to prove that there are elements in the realization of crime in all the legal systems of the world that are immaterial but do not qualify as "mental". Therefore, the "non-mental" elements can be recognized as a true and independent title under the immaterial element with the correct title of "non-mental immaterial elements". Apart from the many benefits of discussing in proving aspect of crimes, this shift has led to a theoretical shift in the fundamental concepts of criminal law, and consequently a change in the structure of all domestic and even foreign law books, and in this sense it is a deconstructing theory. In terms of reasons related to human mental aspect as well as of scrutinizing in the essential elements, crime in action makes it difficult to prove some crimes and by removing certain components from the material element to acquire it, material and sensory means are not sufficient. As a result, it can lead to some kind of diversion or decriminalization and reducing the inflation of the criminal population.